Stirring of sea-ice meltwater enhances submesoscale fronts in the Southern Ocean - Giddy, Isabelle; Swart, S; Du Plessis, Marcel; Thompson, AF; Nicholson, Sarah-Anne (Journal of Geophysical Research: Oceans, 2021)
In the sea-ice-impacted Southern Ocean, the spring sea-ice melt and its impact on physical processes set the rate of surface water mass modification. These modified waters will eventually subduct near the polar front and enter the global overturning circulation. Submesoscale processes modulate the stratification of the mixed layer (ML) and ML properties. Sparse observations in polar regions mean that the role of submesoscale motions in the exchange of properties across the base of the ML is not well understood. The goal of this study is to determine the interplay between sea-ice melt, surface boundary layer forcing, and submesoscale flows in setting properties of the surface ML in the Antarctic marginal ice zone. High-resolution observations suggest that fine-scale lateral fronts arise from either/both mesoscale and submesoscale stirring of sea-ice meltwater anomalies. The strong salinity-driven stratification at the base of the ML confines these fronts to the upper ocean, limiting submesoscale vertical fluxes across the ML base. This strong stratification prevents the local subduction of modified waters by submesoscale flows, suggesting that the subduction site that links to the global overturning circulation does not correspond with the location of sea-ice melt. However, surface-enhanced fronts increase the potential for Ekman-driven cross-frontal flow to modulate the stability of the ML and ML properties. The parameterization of submesoscale processes in coupled-climate models, particularly those contributing to the Ekman buoyancy flux, may improve the representation of ML heat and freshwater transport in the ice-impacted Southern Ocean during summer. 24 © 2021. The Authors. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes Smart Places Ocean Systems and Climate